Entre l’utopie et la diplomatie : Les « contre-décisions » - Barréa, Jean (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
How are cultural changes put forward by so-called 'Utopias' accepted by political elites and then implemented through political decisions or international treaties ? This historical process has often been dealt with via two separate disciplines : sociology and political science. In this article, the author has chosen to use the new paradigm of global politics, i.e., the "issue paradigm", as his general framework of analysis. This article comprises two parts. First a theory of political change - culturally induced. Four concepts of change and progress are examined (Saint-Pierre, Kant, Condorcet and Bentham). This leads the author to the formulation of a new concept: " counter-decision", which can be defined as "a minor concession pulled through socially organized utopian movements from still reluctant political elites, at the very time when History is shaken by some kind of crisis such as war". The total process consists of four successive stages which are: intellectual maturation, socialisation, counter-decision, and new policy which is the final stage of political change culturally induced. The second part of the article gives a historical illustration of this four stages process, examples of which are the European unification, arbitration, collective security, disarmament, arms control, law of war and humanitarian law. These empirical illustrations reveal that Saint-Pierre, Kant, Condorcet and Bentham were all correct in their respective interpretation of progress. It also means that, in politics, cultural progress is at one and the same time rationally thought, reached through a dialectical process, cumulative or determinist in some aspects, if equally debated, and thus voluntarist.